Extensive pedunculated fibrolipoma of the buttocks that had accompanied the patient for 50 years: a rare case report - Yi Jin; Jianmin Li; Jiansong Tang; Zhuoyin Wang (Journal of International Medical Research)
Lipomas are the most prevalent benign soft-tissue tumours, however, pedunculated fibrolipoma in the buttock is rare. Here, the case of a Chinese male patient in his early 70s with a 50-year history of a growing pedunculated fibrolipoma on his right buttock is presented. The attending physician and the registered nurse collaborated on a treatment plan, leading to a successful resection with rhomboid flap transfer. The operation went smoothly, and with continued home care and follow-ups, the patient recovered well, without complications. At 4 months post-surgery, the incision had healed perfectly, boosting the patient’s psychological state and allowing him to resume his daily activities unhindered.